Determination of thermal expansion coefficient for ball grid array using digital image correlation - Kong, Yat Sheng; Crosbie, Liam (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper presents the analysis of coefficient of thermal expansion (CTE) of solder ball on a ball grid array (BGA) through digital image correlation (DIC) technique. The assessment of thermal mechanical properties of semiconductor component is a main challenge due to the sensitivity of micro-scale components to heat. However, the CTE analysis of BGA is significant to address the issues of thermal mismatch strains which lead to failure. Meanwhile, the measurement of solder ball heat expansion is in microscale and heated conditions where the traditional method of strain measurements is ineffective. In this analysis, a micro DIC system was used to measure the strain value of solder balls when it was subjected to temperature loading in a heating stage. The actual temperature of the solder ball was measured using a thermocouple inside the heating stage to ensure uniformity of the temperature. The measured strain during the specific temperature was obtained and plotted for CTE using linear analysis. The average value of CTE for the measured solder ball was 27.33 × 106 / oC. The results indicated that the measurement was close to the reference value of solder ball CTE. This analysis provides a reliable analysis of BGA using a developed DIC method.